2012
DOI: 10.1152/ajprenal.00706.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a serine protease inhibitor on the progression of chronic renal failure

Abstract: The number of the chronic renal failure (CRF) patients is increasing explosively. Hypertension, proteinuria, inflammation, fibrosis, and oxidative stress are intertwined in a complicated manner that leads to the progression of CRF. However, the therapeutic strategies to delay its progression are limited. Since serine proteases are involved in many processes that contribute to these risk factors, we investigated the effects of a synthetic serine protease inhibitor, camostat mesilate (CM), on the progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 48 publications
1
24
0
1
Order By: Relevance
“…CM has successfully been used in experimental models of liver, pancreatic, and renal fibrosis (36)(37)(38), and the antifibrogenic effects of CM were attributable (at least partly) to reduced TGF-b expression and signaling. So far, CM efficiency had never been assessed in pulmonary fibrosis, and our results are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CM has successfully been used in experimental models of liver, pancreatic, and renal fibrosis (36)(37)(38), and the antifibrogenic effects of CM were attributable (at least partly) to reduced TGF-b expression and signaling. So far, CM efficiency had never been assessed in pulmonary fibrosis, and our results are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, CM treatment in the present study was delayed and so is unlikely to interfere with the course of events triggered by bleomycin immediately after its delivery. Moreover, CM is efficient in the abovementioned experimental models of fibrosis affecting other organs, where fibrosis was induced by the administration of different agents (36,37,39,40), surgical procedures (38,41), or even spontaneously (42). Third, the collagen content might be overestimated in the Sircol assay (43).…”
Section: Original Articlementioning
confidence: 99%
“…The fibrotic area was measured as the percentage of blue collagen staining in the tubulointerstitum with the exception of the tubular lumens and vessel walls using the Hybrid Cell Count image analysis (Keyence All-in-One Microscope BZ-X700, Osaka, Japan). To detect the ROS production in the kidney, frozen sections were incubated with DHE as previously described [7]. The images were obtained by an Olympus BX50 with BH2-RFL-T3 (Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress underlies as a common pathogenic component and accelerates the disease progression and complications [4,5,6]. Previously, we demonstrated that camostat mesilate (CM), an orally active synthetic serine protease inhibitor, has renoprotective effects in 5/6 nephrectomized rats [7]. CM showed an antioxidant effect and an antifibrotic effect in the remnant kidney, which resulted in the improvement of the renal function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation